Compensation policy in a large development project: The case of the Bakun Hydroelectric Dam - Lee, Wen Chiat; Viswanathan, K. Kuperan; Ali, Jamal (Routledge, 2014)
Compensation to indigenous communities forced to relocate as a result of a development project is examined in this study.A survey of 379 families displaced by the construction of the Bakun Dam in Sarawak, Malaysia, reveals a high level of dissatisfaction with the compensation provided.The compensation given by the government to the relocated indigenous communities was lower than they had expected. The average compensation gap (the difference between the expected compensation and the actual compensation received for land) is 20 acres per study household.This has resulted in dissatisfaction among the indigenous communities.Greater participation of indigenous communities in the compensation process is needed to reduce the compensation gap.Indigenous communities' rights and freedom to participate in the compensation process is important and should be an integral part of compensation policy for large development projects.